Integrated care: a Scottish perspective - Bruce, David (London J Prim Care (Abingdon), 2015)
The Public Bodies (Joint Working) (Scotland) Act 2014 puts in place the framework for the Integration of health and social care in Scotland. Newly formed health and social care partnerships (HSCP), which will serve as the joint responsibility of NHS boards and local authorities, will work in partnership with the third sector, users, carers and other key stakeholders, including the independent sector. This paper details the underpinning features of the legislation which aims to put ‘personal’ outcomes at the centre, in order for everyone to be able to live longer and healthier lives at home or in a homely setting. Much activity is being undertaken in what is one of the single biggest changes to care services in Scotland.